The Expanding Environments Approach in Elementary Social Studies Education - M. Ramli (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The expanding environments approach (the EEA) is one of the approaches to organizing elementary social studies curriculum. The approach emphasizes the simple concepts that are intimate to students’ environments and then progress toward the complex concepts pertaining to the students’ remote environments as the students move from the first grade to the sixth grade. It has been employed by many social studies educators since the early years of this century and has dominated the organization of social studies curriculum for several decades in the United States Education. This article highlights the description of the EEA and its application to Indonesian elementary social studies education.